Koronare CT-Angiographie und koronare Atherosklerose: Wo stehen wir heute? - Achenbach, Stephan (Herz, 2023)
Cardiac computed tomography (CT) has made substantial progress in recent years. The main field of application is CT coronary angiography for visualization of the coronary arteries and for the detection and exclusion of coronary artery stenosis. This has been included in international guidelines for the management of stable coronary artery disease or chronic coronary syndrome as well as for the diagnostic work-up of patients with acute chest pain; however, it must be taken into account that the diagnostic validity is only sufficiently high when the image quality is good and therefore alternative diagnostic procedures should be included in patients where an unrestricted good image quality is not to be expected. The fact that CT angiography enables the detection not only of coronary stenosis but also of nonobstructive atherosclerotic plaque is interesting for the estimation of the risk of atherosclerotic events. It is practically certain that in the absence of detectable atherosclerotic plaque in CT angiography, statin treatment does not lower the risk of atherosclerotic events. To what extent CT is suitable to provide indications for statin treatment and the threshold for which the presence of nonobstructive plaque should prompt initiation of statin treatment are currently the subject of intensive research.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Acute coronary syndrome; Angiography; Atherosclerosis; Computed tomography; Coronary disease